2017
DOI: 10.1080/00952990.2017.1314488
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use by women during pregnancy does not influence infant DNA methylation of the dopamine receptor DRD4

Abstract: Background: Maternal cannabis use in pregnancy is linked with long-term adverse behavioral outcomes in offspring. Epigenetic processes established in utero that affect dopaminergic (reward) signaling may mediate risks. Associations between cannabis use and offspring DNA methylation have not been investigated; however, maternal tobacco smoking in pregnancy is associated with distinct patterns of DNA methylation at birth and beyond. Objectives: To determine whether maternal cannabis use is associated with methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Another recent study evaluated whether prenatal cannabis exposure is associated with DNA methylation of dopamine receptor D4 ( DRD4 ) promoter in buccal cells from the neonates of maternal subjects with either cannabis or no cannabis use anytime during pregnancy [ 62 •] (Table 1 ). Buccal epithelial cells have the same developmental origins as neuronal cells, and prior studies provide support for buccal cells as a proxy for neurodevelopmental phenotypes [ 63 ].…”
Section: Prenatal Exposure To Cannabis: Epigenetic and Functional Altmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent study evaluated whether prenatal cannabis exposure is associated with DNA methylation of dopamine receptor D4 ( DRD4 ) promoter in buccal cells from the neonates of maternal subjects with either cannabis or no cannabis use anytime during pregnancy [ 62 •] (Table 1 ). Buccal epithelial cells have the same developmental origins as neuronal cells, and prior studies provide support for buccal cells as a proxy for neurodevelopmental phenotypes [ 63 ].…”
Section: Prenatal Exposure To Cannabis: Epigenetic and Functional Altmentioning
confidence: 99%
“…There was no association between DNA methylation at individual CpG sites in DRD4 after correction for multiple testing. It is unclear if the null findings were due to the relatively small sample size ( n = 804 maternal subjects), the tissue specificity, or a lack of biological relevance [ 62 •]. Certain genetic polymorphisms of DRD4 increase risk of drug use and severity of ADHD symptoms in children, both of which have been associated with cannabis exposure [ 64 ].…”
Section: Prenatal Exposure To Cannabis: Epigenetic and Functional Altmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study looked at cannabis effect on infants' DNA methylation in the dopamine receptor promoter at CpG units. There was no significant evidence that cannabis impacted the methylation in these specific areas [41].…”
Section: Epigenetics and Cannabismentioning
confidence: 99%
“…On the other hand, a longitudinal pregnancy cohort of 1634 families studied effects of perinatal maternal gestational cannabis on infants' health through investigating offspring DNA methylation. The study focused on the offspring dopamine receptor gene DRD4 promoter in infants, and found that there is no potential inherited risk in the infants [41]. The study suggested that investigating a larger sample and other genes might have different results [41].…”
Section: Epigenetics and Neuronal Development With Alcohol/ethanol An...mentioning
confidence: 99%